2016
DOI: 10.1186/s13068-016-0583-1
|View full text |Cite
|
Sign up to set email alerts
|

A new laboratory evolution approach to select for constitutive acetic acid tolerance in Saccharomyces cerevisiae and identification of causal mutations

Abstract: BackgroundAcetic acid, released during hydrolysis of lignocellulosic feedstocks for second generation bioethanol production, inhibits yeast growth and alcoholic fermentation. Yeast biomass generated in a propagation step that precedes ethanol production should therefore express a high and constitutive level of acetic acid tolerance before introduction into lignocellulosic hydrolysates. However, earlier laboratory evolution strategies for increasing acetic acid tolerance of Saccharomyces cerevisiae, based on pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(63 citation statements)
references
References 88 publications
(98 reference statements)
2
59
0
2
Order By: Relevance
“…Several previously published adaptive evolution approaches of S.   cerevisiae (such as for acetic acid and n-butanol tolerance) have shown that strains evolved in parallel experiments can have mutations affecting different sets of genes [44, 45]. Therefore, the results of the current study strongly suggest that UBR2 and GUT1 are absolutely crucial in the establishment of glycerol utilization capability in CEN.PK strains.…”
Section: Discussionsupporting
confidence: 51%
“…Several previously published adaptive evolution approaches of S.   cerevisiae (such as for acetic acid and n-butanol tolerance) have shown that strains evolved in parallel experiments can have mutations affecting different sets of genes [44, 45]. Therefore, the results of the current study strongly suggest that UBR2 and GUT1 are absolutely crucial in the establishment of glycerol utilization capability in CEN.PK strains.…”
Section: Discussionsupporting
confidence: 51%
“…Adaptive evolution is a powerful tool, which uses the ability of micro‐organisms to adapt to environmental changes, in order to improve strains for various biotechnological applications (Wallace‐Salinas and Gorwa‐Grauslund ; Culleton et al ; González‐Ramos et al ; Patyshakuliyeva et al ). Most of the current filamentous fungi obtained through adaptive evolution were created for increased enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a Saccharomyces cerevisiae strain was created with improved tolerance to higher temperature and hydrolysate‐derived inhibitors for second generation ethanol production (Wallace‐Salinas and Gorwa‐Grauslund ). Another example was the S. cerevisiae strains that were created with increased acetic acid tolerance to withstand the negative effects of acetic acid released during hydrolysis of lignocellulosic feedstocks for bio‐ethanol production (González‐Ramos et al ). Evolutionary adaptation depends on spontaneous mutation(s) that is beneficial under the selection condition (Schoustra et al ; Schoustra and Punzalan ).…”
Section: Introductionmentioning
confidence: 99%
“…CEN.PK113-7D is a haploid strain used as a model organism in biotechnology-related research and systems biology because of its convenient growth characteristics, its robustness under industrially relevant conditions and its excellent genetic accessibility (Canelas et al 2010;Nijkamp et al 2012;González-Ramos et al 2016;Papapetridis et al 2017). CEN.PK113-7D was sequenced using a combination of 454 and Illumina short-read libraries, and a draft genome was assembled consisting of over 700 contigs (Nijkamp et al 2012).…”
Section: Introductionmentioning
confidence: 99%